PA.01 Successful implementation of WHO hand hygiene strategy in a Ugandan obstetric unit. (9th June 2014) - MacLeod, K; Khairudin, D
Abstract : Worldwide, one death in three is from an infectious or communicable disease. Almost all these deaths occur in resource poor countries. Hand washing may be one of the most cost effective means of preventing infection in this area. The World Health Organisation (WHO) developed a concept called 'My five moments for hand hygiene'. This designated moments when hand hygiene was required and provided tools to facilitate education and minimise inter-individual variation. We introduced a hand hygiene strategy in a Ugandan Obstetric Unit with 7000 deliveries a year. We formed a hand hygiene committee to facilitate education and give performance feedback. Sinks were installed to improve sink to bed ratio and reminders were posted in the clinical areas. WHO observation forms were used to collect data and perform compliance calculations. 294 opportunities for hand hygiene were recorded. Overall compliance rose from 22.4% to 47.6% following implementation (p < 0.05). Interns and midwives showed the biggest overall improvement in hand hygiene. Improving hand hygiene is effective and achievable in resource poor settings.